Human Hippocampal and Parahippocampal Theta during Goal-Directed Spatial Navigation Predicts Performance on a Virtual Morris Water Maze - Cornwell, Brian R. (Society for Neuroscience, 2008)
The hippocampus and parahippocampal cortices exhibit theta oscillations during spatial navigation in animals and humans, and in the former are thought to mediate spatial memory formation. Functional specificity of human hippocampal theta, however, is unclear. Neuromagnetic activity was recorded with a whole-head 275-channel magnetoencephalographic (MEG) system as healthy participants navigated to a hidden platform in a virtual reality Morris water maze. MEG data were analyzed for underlying oscillatory sources in the 4–8 Hz band using a spatial filtering technique (i.e., synthetic aperture magnetometry). Source analyses revealed greater theta activity in the left anterior hippocampus and parahippocampal cortices during goal-directed navigation relative to aimless movements in a sensorimotor control condition. Additional analyses showed that left anterior hippocampal activity was predominantly observed during the first one-half of training, pointing to a role for this region in early learning. Moreover, posterior hippocampal theta was highly correlated with navigation performance, with the former accounting for 76% of the variance of the latter. Our findings suggest human spatial learning is dependent on hippocampal and parahippocampal theta oscillations, extending to humans a significant body of research demonstrating such a pivotal role for hippocampal theta in animal navigation.